2011
DOI: 10.1007/s12126-011-9113-4
|View full text |Cite
|
Sign up to set email alerts
|

Dimensions of Psychological Well-being Predict Consistent Condom Use among Older Adults Living with HIV

Abstract: This study examined the role of psychological well-being in promoting consistent condom use among a sample of HIV-positive adults ages 50 and older living in New York City. Data were drawn from the Research on Older Adults with HIV (ROAH) project, and 328 sexually active participants (ages 50 to 78) were included in this cross-sectional analysis. Participants completed the Ryff Scales of Psychological Well-being (Ryff Journal of Personality and Social Psychology 57 (6): [1069][1070][1071][1072][1073][1074][107… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 47 publications
0
9
0
Order By: Relevance
“…In the Research on Older Adults with HIV (ROAH) study, more than one-third of sexually active older adults with HIV reported engaging in condomless sex, and 18% reported condomless sex with a serodiscordant partner (Golub et al, 2011; Golub et al, 2010; Karpiak & Brennan, 2009). In a longitudinal analysis, using data also from the Women’s Interagency HIV Study (WIHS), we found that 22–25% of women living with HIV, regardless of viral suppression, exhibited moderate to high levels of condomless sex after 13 years (Taylor et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…In the Research on Older Adults with HIV (ROAH) study, more than one-third of sexually active older adults with HIV reported engaging in condomless sex, and 18% reported condomless sex with a serodiscordant partner (Golub et al, 2011; Golub et al, 2010; Karpiak & Brennan, 2009). In a longitudinal analysis, using data also from the Women’s Interagency HIV Study (WIHS), we found that 22–25% of women living with HIV, regardless of viral suppression, exhibited moderate to high levels of condomless sex after 13 years (Taylor et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Older adults with HIV are particularly isolated from supportive social networks and are less likely to disclose their status due to the double stigma of AIDS and ageism, both of which lead to stress and poorer mental health outcomes [70–74]. To compensate for these changes, many older adults use alcohol, tobacco, and/or illicit drugs which are factors for sexual risk [14, 7577]. These changing psychosocial and intrapersonal factors highlight the need to understand the context of sexual behavior among older women with HIV.…”
Section: Discussionmentioning
confidence: 99%
“…Another study in South Africa demonstrated that lack of HIV disclosure to partner, and alcohol use at last sex were correlated with unprotected intercourse. 2 Other variables found to be associated with more condom use in this population include higher education level, 4 economic stability, 5 psychological well-being, 6 and relationship characteristics such as HIV status of partner, length of relationship, and desire for children. 5 However, there is limited literature on whether or not the determinants of condom use differ between male and female HIV-infected individuals.…”
mentioning
confidence: 89%